99.0k views
4 votes
PLEASE HELP ASAP!!! CORRECT ANSWER ONLY PLEASE!!!

Simplify.

Assume x and z are nonnegative.

PLEASE HELP ASAP!!! CORRECT ANSWER ONLY PLEASE!!! Simplify. Assume x and z are nonnegative-example-1

1 Answer

5 votes


3√(32x^4z)=3√(32)\cdot√(x^4)\cdot√(z)=3√(16\cdot2)\cdot√((x^2)^2)\cdot√(z)\\\\=3√(16)\cdot\sqrt2\cdot x^2\cdot√(z)=3\cdot4\cdot√(2)\cdot x^2\cdot√(z)\\\\=12x^2√(2z)\\\\\text{Used:}\\\\√(a\cdot b)=√(a)\cdot√(b)\\\\√(a^2)=a\\\\(a^n)^m=a^(n\cdot m)

User Rathi J
by
5.6k points